The relation between gender and access to dental services and goods - Maria Vieira de Lima Saintrain; Paulo Leonardo Ponte Marques; Lúcio Hélio Pereira de Almeida; Caroline Barbosa Lourenço; Raimunda Magalhães da Silva; Anya Pimentel Gomes Fernandes Vieira (Universidade de Fortaleza, 2014)
ABSTRACT The Brazilian National Health System guarantees universal access to health services. However, this universal access is not always achieved, making relevant studies that evaluate access to health care and the way gender influence this access. Objective: Identify the influence of gender in the access to dental services and goods such as consultation, toothbrush, toothpaste and dental prostheses use in Brazil's Northeast region. Methods: Cross-sectional, quantitative and population coverage study, with the population of Guaiuba municipality. Data were collected by Community Health Agents from July 2007 to February 2008. We used the Community Oral Health Indicator to verify the access to oral health services, oral hygiene, dental visit, use and need of dental prosthesis. Data were analyzed using SPSS 15.0 software, using the chi-square test and significance level of 5%. Results: 2581 people participated, with a mean age of 24.42 years (SD± 19, 365), with 1628 female (63.1%). Among the interviewees, 2,341 (90.7%) had access to a toothbrush, 2272 (88.0%) to toothpaste, and 1175 (45.5%) to a dental appointment. The need for dental prosthesis was higher in women, 581 (35.7%) versus 221 (23.2%) men and their access [354 (60.9%)] versus [96 (43.4%)] with p<0.05. Conclusion: The access to health services and dental treatment presents gender as an influence factor. Women have most of the needs and benefits. The edentulism affects mostly the population with a poor access to dental prosthesis.